Glucose utilization during exercise: influence of endurance training - Wojtaszewski, J. F.; Richter, E. A. (Acta Physiologica Scandinavica, 1998)
During exercise skeletal muscle glucose utilization is higher than at rest. This is due to the combined effect of an increase in glucose supply, increased surface membrane glucose transport capacity and increased muscle glucose metabolism during exercise. The kinetics of glucose utilization in skeletal muscle during exercise in humans show an apparent Km of approximately 10 mM, indicating that changes in the blood glucose concentration around the physiological level of approximately 5 mM almost linearly translate into changes in muscle glucose utilization. The signalling events responsible for increased glucose transport in contracting muscle are not well understood, although calcium seems to be involved. Contractions do not utilize the proximal part of the insulin signalling cascade to activate glucose transport, because contractions do not cause phosphorylation of insulin receptor substrate 1 or activation of phosphatidylinositol 3-kinase. Endurance training leads to a decrease in glucose utilization during submaximal exercise of a given absolute submaximal power output in spite of a large increase in the total muscle GLUT4 content. The molecular mechanism behind this decrease in glucose utilization seems to be blunted exercise-induced translocation of GLUT4 protein to the sarcolemma, in turn blunting the exercise-induced increase in sarcolemmal glucose transport capacity.